Soluble urokinase plasminogen activator receptor informs on the progression course after multiple injuries. (2nd October 2016) - Patrani, Maria; Tsaganos, Thomas; Kotzampassi, Katerina; Paraschos, Michael; Katsenos, Chrysostomos; Giamarellos-Bourboulis, Evangelos J.; Mandragos, Konstantinos
Abstract: Purpose: The purpose of this study is to study the use of soluble urokinase plasminogen activator receptor (suPAR) for the prognosis of multiple organ dysfunction (MOF) after multiple traumas. Methods: Serum suPAR was measured within the first 24 h after multiple injuries in 85 patients. Measurements were repeated after 4 d or at sepsis onset. Results: Odds ratio for trauma-associated MOF was 4.09 ( p : 0.026) with admission suPAR greater than 8 ng/ml. More than 40% increases of suPAR were associated with odds ratio 9.33 ( p : 0.047) for severe sepsis. Conclusions: suPAR is a useful surrogate biomarker for development of MOF and severe sepsis after multiple traumas.